Binlerce yıllık uygarlıkların merkezi, Osmanlı İmparatorluğu'nun ilk başkenti, bereketli topraklarda yükselen güzellikler kenti : Bursa = The center of ancient civilisations, the first capital of Ottoman empire, the city of natural beauties arising on fertile lands : Bursa (Ankara)
262 s.